Bordi periurbani e sincronicità nel paesaggio. Un progetto di ri-significazione per il Vallone San Rocco nel Parco delle Colline di Napoli - Bernieri, Adriana; Castaldi, Simone (Ri-Vista. Research for landscape architecture, 2024)
As part of design research that investigates new balances between man and ecosystems, the theme of the margins between metropolis and rural spaces represents an important field of experimentation. These borders appear as pulverized and discontinuous urban fabrics, made of abandoned places, agricultural areas, fragments of a landscape whose components are difficult to identify and whose unveiling, in habitable forms and new typology ecosystem logics, is precluded by a dense system of barriers and fences. The article explores these themes starting from some consolidated bibliographic and design approaches, going through a proposal for the re-signification of the edges of the Vallone San Rocco, a naturalistic area in the northern part of the city of Naples included in the Metropolitan Park of the Hills, through the recovery of interrupted ecosystems and the rediscovery of a cultural landscape of great importance for both the city and the region.